Pengelolaan dan Pemanfaatan Sampah Rumah Tangga: Studi Kasus Bank Sampah Sakinah di Kelurahan Batu Gadang - Yulia, Regina; Yunarti, Yunarti; Syahrizal, Syahrizal (Department of Anthropology, 2024)
This study describes the management and utilization of household waste in the Sakinah Waste Bank. Waste banks are present as an alternative in household waste management, expected to help overcome waste management problems and reduce the amount of waste in landfills. This research aims to look at the management of household waste in the Sakinah Waste Bank, as well as the utilization of household waste through the Sakinah Waste Bank in the Batu Gadang Village community. This research uses a qualitative method with a case study approach, then uses data collection techniques in the form of observation, interviews, literature study, and documentation. The selection of informants was carried out using purposive sampling technique, with a total of 15 informants, consisting of 10 key informants and five ordinary informants. The results showed that the management of household waste in the Sakinah Waste Bank, there is a change in the view of waste from dirty and useless items to items that can be reprocessed. through the Sakinah Waste Bank, the community is educated on how to manage plastic recycled waste so that it will produce economic value for the community, especially customers of the Sakinah Waste Bank. The existence of the Sakinah Waste Bank also makes changes in the community, starting from the view of waste, the habit of managing waste to the economic benefits felt by the community.Abstrak: Penelitian ini menjelaskan tentang pengelolaan dan pemanfaatan sampah rumah tangga di Bank Sampah Sakinah. Bank sampah hadir sebagai alternatif dalam pengelolaan sampah rumah tangga, diharapkan dapat membantu mengatasi permasalahan pengelolaan sampah dan berkurangnya jumlah sampah di tempat pembuangan akhir. Penelitian ini bertujuan melihat pengelolaan sampah rumah tangga pada Bank Sampah Sakinah, serta pemanfaatan sampah rumah tangga melalui Bank Sampah Sakinah di masyarakat Kelurahan Batu Gadang. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, kemudian menggunakan teknik pengempulan data berupa observasi, wawancara, studi pustaka, dan dokumentasi. Pemilihan informan dilakukan dengan teknik purposive sampling, dengan total 15 informan, yang terdiri dari 10 informan kunci dan lima informan biasa. Hasil penelitian menunjukan bahwa pengeloaan sampah rumah tangga di Bank Sampah Sakinah, adanya perubahan pandangan terhadap sampah yang awal yang barang kotor dan tidak berguna menjadi barang yang dapat diolah kembali. melalui Bank Sampah Sakinah masyarakat diedukasi mengenai cara pengelolaan sampah daur ulang plastik hingga nantinya menghasilkan nilai ekonomis bagi masyarakat khususnya nasabah Bank Sampah Sakinah. Keberadaan Bank Sampah Sakinah juga membuat perubahan yang ada dimasyarakat mulai dari pandangan mengenai sampah, kebiasaan mengelola sampah hingga manfaat ekonomis yang dirasakan masyarakat.